The Issue of Polygamy in Islamic Family Law: Between Tradition and Gender Justice on the International Stage - Fahira, Siti Hapsah (Journal of Islamic Family Law, 2025)
The issue of polygamy in Islamic family law has become a complex topic of debate, particularly concerning gender equality and women's rights in the context of international law. Although polygamy is permitted under Islamic law, its application often conflicts with the gender equality principles expected in modern societies. This study aims to analyze the dynamics between Islamic family law traditions and international demands for gender justice regarding the practice of polygamy. The objective of this research is to understand how Islamic family law regulates polygamy and its impact on gender justice, as well as to explore how countries with Muslim majorities adapt international principles concerning women's rights in the practice of polygamy. This research employs a descriptive qualitative approach, utilizing data collection techniques that include in-depth interviews and document analysis. The countries selected for this study are Indonesia, Saudi Arabia, the United Arab Emirates, and Turkey, which represent various legal approaches to polygamy. The study reveals that while there are restrictions on the application of polygamy in some countries, the practice continues to create tension between tradition and gender equality demands. Countries with Muslim majorities need to reform their policies to protect women's rights and ensure that Islamic family law can be adapted in line with international principles.